Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1002/1097-0142(19890601)63:11<2156::aid-cncr2820631115>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GCDFP-15 in breast carcinomas. Relationship to pathologic and clinical factors

Abstract: A retrospective immunoperoxidase staining study for a glycoprotein isolated from human breast gross cystic disease fluid (GCDFP-15) in 562 primary breast carcinomas in 539 patients was conducted to correlate its immunohistochemistry with pathologic and clinical factors. Overall, 55% of the carcinomas studied stained positively for GCDFP-15. In certain histologic subtypes, the percentage of carcinomas that stained positively was greater: those subtypes with apocrine histologic features (75%), intraductal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 5 publications
2
49
0
1
Order By: Relevance
“…Given the low incidence and clinical distinctiveness of tumours arising from other source tissues, PIP/GCDFP-15 protein has already been considered as a breast cell specific marker, complementary to keratin (de Almeida & Pestana 1992). This potential is based on the fact that PIP expression can be detected by IHC in up to 76% of breast carcinomas (Wick et al, 1989) and there is a high degree of concordance between PIP expression in 1°primary carcinomas and nodal metastases (Mazoujian et al, 1989). Expression of this marker has been associated with apocrine differentiation, but there is not a direct concordance with Muc1 (Soomro & Shousha, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low incidence and clinical distinctiveness of tumours arising from other source tissues, PIP/GCDFP-15 protein has already been considered as a breast cell specific marker, complementary to keratin (de Almeida & Pestana 1992). This potential is based on the fact that PIP expression can be detected by IHC in up to 76% of breast carcinomas (Wick et al, 1989) and there is a high degree of concordance between PIP expression in 1°primary carcinomas and nodal metastases (Mazoujian et al, 1989). Expression of this marker has been associated with apocrine differentiation, but there is not a direct concordance with Muc1 (Soomro & Shousha, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We estimate therefore that the true frequency of PIP mRNA positive primary tumours is approximately 85% of cases. This is consistent with our data where PIP mRNA expression was detected in approximately 70% nodal metastases (Table 2) and that of others (Mazoujian et al, 1989) and the fact that PIP expression is often conserved between primary and nodal metastases ( Figure 1B), as also documented by others (Mazoujian et al, 1989;Wick et al, 1998). The presence of PIP mRNA in lymph nodes that are histologically negative (on the basis of assessment of a single haematoxylin and eosin (H&E)-stained diagnostic section) may suggest the presence of occult metastases (Ferrari et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ER expression is exceedingly rare in adenocarcinomas of the GI tract, especially colorectal adenocarcinomas. [21][22][23][24] GCDFP-15 and Mammaglobin A.-The GCDFP-15, as described by Mazoujian and colleagues, 25 exhibited an overall sensitivity of approximately 55% in breast carcinomas, 26 and in more-recent studies the reported sensitivity (using different monoclonal and polyclonal antibodies) has been between 23% and 73%. [27][28][29] In our experience, using the 23A3 monoclonal antibody, the sensitivity is close to 80%.…”
Section: Breast Cancer Markersmentioning
confidence: 99%
“…Prolactin signalling is essential for lobuloalveolar differentiation at pregnancy (Grimm et al 2002 and central to the function of HS-MECs during early pregnancy to promote the expression of paracrine growth factors associated with alveolar cell differentiation (Dontu et al 2004, Mukherjee et al 2010, Tarulli et al 2013, and significant cross-talk between prolactin and progesterone pathways has been reported (Lee & Ormandy 2012, Obr et al 2013. Importantly, expression of PIP has been associated with breast tumours with apocrine features, a subtype with an important emergent role for AR regulation of tumour growth (Mazoujian et al 1983, 1989, Farmer et al 2005, Doane et al 2006.…”
Section: Integration Of Notch and Armentioning
confidence: 99%